Synthesis and Anti-Corrosion Resistance of Polyacrylonitrile-Based Nanocomposites with Moringa-Extracted Nickel and Vanadium Oxide Nanoparticles - Sarah Saadi Ahmed; Nada Mutter Abbass (Iraqi Journal of Physics)
This study aims to enhance the corrosion resistance of carbon steel (45 alloys) in saline water (3.5% NaCl) by applying a polymer nanocomposite coating. The nanocomposite was synthesized by integrating nickel oxide (NiO) and vanadium oxide (V₂O5) nanoparticles, produced via a green synthesis method using moringa extract, into a polyacrylonitrile (PA) matrix. The coating's performance was evaluated across a range of temperatures: 293, 303, 313, and 323 K, achieving an inhibition efficiency of up to 89% at 303 K. The created nanocomposites were carefully examined using various testing methods, such as atomic force microscopy (AFM), Fourier transform infrared spectroscopy (FT-IR), transmission electron microscopy (TEM), X-ray diffraction (XRD), thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC). AFM analysis revealed particle sizes of 44.5 nm for NiO and 54.47 nm for V₂O5, while TEM images indicated nonhomogeneous spherical morphologies. FT-IR and XRD showed that the nanoparticles were successfully added to the polymer, and TGA/DSC tests proved that the nanocomposites can withstand high temperatures. The results indicate that these nanocomposites could be very useful as strong corrosion protectors, improving the safety of carbon steel in harsh conditions.